Kitab Hadis Nusantara dan Empat Pilar Kebangsaan: Studi Pemikiran KH. Asrori Dalam Kitab Al-Bayān Al-Muṣoffā Fī Waṣiyat Al-Muṣṭofā - Hartati Hartati (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This article discusses one of the books of Indonesian hadith and KH Asrori's thoughts on the Indonesian people's way of life (the four pillars of nationality). These four bases exist from several state concepts, including from the trials politica Montesquieu (1689 AD), on the other hand, al-Mawardi (974-1058 AD) has previously issued about state politics in the book al-Aḥkām al-Sulṭāniyyah. Indonesian intellectuals widely studied this book, and then this country combined it into four pillars of nationality (UUD 1945, Pancasila, Bhineka Tunggal Ika and NKRI). National figures and scholars have read and studied it, and KH Aurora is one of the thousands of students who later gave birth to many works, one of which was the book al-Bayān al-Muṣoffā fī Waṣiyat al-Muṣṭofā. The research aims to prove that the book contains four pillars of nationality. The method used is qualitative - library research with a historical paratext approach. The primary data source is taken from the studied book, while the supporting data comes from the related text. The data analysis technique is carried out by searching and tracking books related to one work with existing works. The results show that this archipelago of hadith books includes the ancient manuscripts that have been printed and the position of the book as syarah from the book